Risk endogeneity at the lender/investor-of-last-resort - Diego Caballero; André Lucas; Bernd Schwaab; Xin Zhang (European Central Bank (ECB), 2019)
We address the question to what extent a central bank can de-risk its balance sheet by unconventional monetary policy operations. To this end, we propose a novel risk measurement framework to empirically study the time-variation in central bank portfolio credit risks associated with such operations. The framework accommodates a large number of bank and sovereign counterparties, joint tail dependence, skewness, and time-varying dependence parameters. In an application to selected items from the consolidated Eurosystem's weekly balance sheet between 2009 and 2015, we find that unconventional monetary policy operations generated beneficial risk spill-overs across monetary policy operations, causing overall risk to be nonlinear in exposures. Some policy operations reduced rather than increased overall risk.
Keywords: G21; C33; 330; Credit risk; risk measurement; central bank; lender-of-last-resort; unconventional monetary policy